Knowledge versus content in e-learning: a philosophical discussion! - Costa, Gonçalo Jorge Morais da (2014)
Historically education has been supported by technology; however, during the past three decades electronic technologies for educational purposes have been used to achieve better learning outcomes. In fact, there are two main issues in using computers for educational purposes; that is, people learn “from” or “with” technologies. The e-learning literature reveals that technological and instructional perspectives had been widely diffused, with ethical and cultural issues only being considered more recently. The aim of this paper is to discuss a blurred distinction, which entails into all these fields of research: how do we define knowledge and content in an e-learning project?